How to handle conflict & manage anger [soundrecording] - Waitley, Denis (New York Simon & Schuster, 1994)
Social interaction is wrought by tension and conflict. This motivational audio program teaches how controlling anger is essential to personal success.
Keywords: Conflict management; Anger; Control (Psychology).; Emotions; Stress, Psychological; Psychology; Sociology